The distribution patterns and community structure of the Tsitsikamma rocky littoral ichthyofauna - Burger, Lynton Francois (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1991)
The results of a community survey of the rocky intertidal and subtidal reef ichthyofauna of the Tsitsikamma National Park and adjacent areas are presented. An updated species checklist is given, comprising 116 species of 46 families, including a new genus and species of Tripterygiid. Single species are shown to dominate, in terms of numbers, both the cryptic and subtidal components for all the areas sampled down the vertical profile. Species richness, evenness and diversity are found to increase with depth for both the cryptic and suprabenthic components. A community level feeding study shows an increase in trophic specialisation with depth and food availability is found to be an important factor delimiting littoral fish vertical distribution. The nursery function of the Tsitsikamma rocky littoral area is assessed and it is shown that shallow littoral areas as a whole are more important than intertidal pools alone in functioning as nurseries. The results of the study are found to fit into the existing trend of an increase in species richness and diversity, from west to east, along the South African coast. A significant difference is shown between the observed frequencies of species on exploited reefs outside the Park and unexploited reefs inside the Park. The density of the key reef predator Petrus rupestris is shown to be nine times more abundant on deep reef inside the park compared to deep reef outside the park (0.0045 fish/mÂ² and 0.0005 fish/mÂ² respectively) and a paucity of larger individuals of this species on exploited reefs is noted. Marked differences in the relative abundance of other species between exploited and unexploited reefs are evident and it is hypothesised that community disruption has occurred on exploited reefs, either directly or indirectly because of the removal of P. rupestris. These results are discussed in the context of marine reserves as a conservation strategy and a recommendation is made to extend the 5.6km seaward boundary of the Tsitsikamma National Park westwards to include the large concentration of presently exploited rocky reefs between the Blaaukrans river mouth and Natures Valley.
Keywords: Fishes -- South Africa -- Geographical distribution; Tripterygiidae -- South Africa -- Geographical distribution; Littoral plants -- South Africa -- Tsitsikamma; Littoral plants